Patient satisfaction with pharmaceutical services in Brazilian primary health care - Orlando Mario Soeiro; Noêmia Urruth Leão Tavares; José Miguel do Nascimento Júnior; Augusto Afonso Guerra Junior; Ediná Alves Costa; Francisco de Assis Acurcio; Ione Aquemi Guibu; Juliana Álvares; Margô Gomes de Oliveira Karnikowski; Silvana Nair Leite; Karen Sarmento Costa (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To evaluate patient satisfaction with pharmaceutical services in Brazilian primary health care. METHODS This is a cross-sectional, exploratory, and evaluative study on a representative sample from the five Brazilian geopolitical regions resulting from the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos - Serviços, 2015 (PNAUM - National Survey on Access, Use and Promotion of Rational Use of Medicines - Services, 2015). The outcome was the patient's satisfaction, obtained using the item response theory. Associations were tested using Pearson's Chi-square test with sociodemographic and health variables, and multiple logistic regression analyses were carried out. The Hosmer-Lemeshow test was used to verify the adequacy of the final model. Logistic regression results were presented as odds ratio. RESULTS The overall percentage of patients satisfied with these services was 58.4% (95%CI 54.4-62.3). The "opportunity/convenience" aspect had the lowest satisfaction percentage (49.5%; 95%CI 46.4-52.6) and "interpersonal aspects," the highest percentage (90.5%; 95%CI 88.9-91.8), significantly higher than other aspects. Sex, age group, limitations due to disease, and self-perception of health remained associated in the final multiple logistic model regarding general satisfaction. CONCLUSIONS Most of the interviewed users were satisfied with pharmaceutical services in Brazilian cities, and the satisfaction with the customer's service was determinant in the patient's overall satisfaction.